Chaetomitrium Lauterbachii - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are rather laxly branched; (2) branch leaves are slightly flattened, rather lax, concave, long-acuminate, and constricted below apices; (3) leaf margins are serrate above with simple teeth and denticulate below; (4) lamina cells are laxly spinose-prorate above and prorate below.